English Presence in Our Landscape: A Global Community at Play - Khristianto Khristianto; Arif Budiman; Maulana Mualim (Faculty of Social and Political Sciences University of Bangka Belitung, 2022)
English today is everywhere in our landscape. It appears in every commercial item. People seem to have a strong belief that language has an extra magical power to sell; it contains a powerful mantra to persuade consumers to choose their products. With its extensive use, English marks a kind of global community. This study makes an online survey through Street View in Google Maps to collect data on the use of English in the landscapes, particularly in the area of Simpang Lima, Semarang. This employs a perspective of language ecology questioning the ideology behind the rampant English, dominating our place. Based on the data collected, it proves that English appears the most. English is found on the billboards of automotive, mobile phones, cosmetic products, cigarettes, electronics, online shops, internet-based transportation services, housing complexes/real estate, and cellular providers. English items are equal to Indonesian. In Indonesian ads, English many times is featured to be a tagline. Meanwhile, English ads give no space for Indonesian items. Here, English surely does not symbolize the language of the community. We do believe that Semarang is dominantly occupied by Indonesian people. However, it is proved that English has shown its domination in the space, with no real users in the field. It is there for its commercials effects and association, based on the shared assumption of its prestige, modernity, beauty and power.